PENGGUNAAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA MATERI SISTEM PERSAMAAN LINEAR TIGA VARIABEL (SPLTV) KELAS X MIPA 1 SMA NEGERI 1 BOJONGMANGU - Ipah Muzdalipah; Sri Wahyuni; Yayat Hidayat (LPPM Universitas Advent Indonesia, 2024)
This research was motivated by the low mathematics learning outcomes of students in class X MIPA-1 SMAN 1 Bojongmanggu, Bekasi Regency. Based on the results of the final evaluation of the 2021/2022 academic year, information was obtained that more than 50% of students obtained mathematics scores below the established KKM standards. To overcome this problem, Classroom Action Research (CAR) was carried out with the aim of improving students' mathematics teaching and learning outcomes using the Problem Based Learning. This research involved 36 students of class X MIPA 1 SMAN 1 Bojongmangu Bekasi Regency. This research was carried out on 5-26 September 2022 on the material Systems of Linear Equations with Three Variables. This research was carried out in 2 cycles, each cycle including stages: planning, implementation, observation and reflection. The instruments used in this research include: a set of test evaluation, observation instrument, and questionnaires. The research results showed that there was an increase in learning outcomes by 21.66%, where in cycle I the completeness of learning outcomes was 66.67%, while in cycle II the completeness of learning outcomes reached 88.33%. These results show that the application of the Problem Based Learning model can improve students' mathematics learning outcomes.